2013
DOI: 10.4236/jbnb.2013.41006
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Cellulose Whiskers from Kenaf (<i>Hibiscus cannabinus</i> L.) Bast Fibers

Abstract: Cellulose whiskers were isolated from kenaf (Hibiscus cannabinus L.) bast fibers via sulfuric acid and hydrochloric acid hydrolysis. Raw kenaf bast, NaOH treated, bleached fibers, sulfuric acid whiskers (SAW) and hydrochloric acid whiskers (HClW) morphology, functional groups, crystallinity, and thermal stability were characterized. The TEM images showed that the sulfuric acid and HCl whiskers have average diameters and length range of 3 nm and 100 -500 nm, respectively. The FTIR study indicated that during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
2
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 37 publications
2
33
2
12
Order By: Relevance
“…Chemical treatment is the most effective way to obtain a higher purity cellulose. A combination of chlorite bleaching, alkali treatment, and acid hydrolysis is the most common process used to extract cellulose from the plants (Habibi et al 2010;Liu et al 2010;Rosa et al 2010;Siqueira et al 2010;Chen et al 2012;Kargarzadeh et al 2012;Sheltami et al 2012;Zaini et al 2013). Chlorite bleaching has the function of extracting holocellulose from raw cellulose fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical treatment is the most effective way to obtain a higher purity cellulose. A combination of chlorite bleaching, alkali treatment, and acid hydrolysis is the most common process used to extract cellulose from the plants (Habibi et al 2010;Liu et al 2010;Rosa et al 2010;Siqueira et al 2010;Chen et al 2012;Kargarzadeh et al 2012;Sheltami et al 2012;Zaini et al 2013). Chlorite bleaching has the function of extracting holocellulose from raw cellulose fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Constant magnetic stirring combined with acid hydrolysis in H 2 SO 4 played a significant role in reducing fiber length and diameter. The fiber size resulted in this study was larger than that reported in [1,3] due to no mechanical treatments with a homogenizer [1] or a high frequency vibrator [3] were done.…”
Section: Resultsmentioning
confidence: 80%
“…The non-cellulosic components almost completely dissolved in 6% NaOH and led to homogeneous surface roughness and fibers with clean surface. The concentration of alkali used in this study was slightly higher than used previously [1,3]; the concentration of H 2 SO 4 was lower than in [1], but similar to that used in [3]. Constant magnetic stirring at 350 rpm was done during acid hydrolysis (H 2 SO 4 ).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations